2018
DOI: 10.18203/2394-6040.ijcmph20181217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of dyslipidemia among male industrial workers in India

Abstract: Background: Lipid Abnormalities are major risk factors for coronary artery diseases. Prevalence of dyslipidemia is high in India shown by various studies due to lifestyle changes. This study was conducted to estimate the prevalence of dyslipidemia and its association with body fat percentage, body mass index, diabetes, tobacco use and hypertension.Methods: A cross-sectional study was conducted among 300 male employees from a packaging and binding industry in Maharashtra. Behavioural data, anthropometric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
3
5
5
Order By: Relevance
“…The present finding is consistent with the results reported in Palestine (66.4%) [18] and South Africa (67.3%) [19]. However, the prevalence of dyslipidemia in this study is higher than the previous findings reported in Eastern Ethiopia (34.8%) [11], Africa PLOS ONE (25.5%) [9], China (32.2%) [20], Iran (30.0%) [21], India (50.7%) [22], and Uganda (63.3%) [23]. Contrary to this, the prevalence is lower than previous studies reported in Lithuania (89.7%) [24], South Africa (85.0%) [25], India (78.4%) [26] and Poland (77.2%) [27].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…The present finding is consistent with the results reported in Palestine (66.4%) [18] and South Africa (67.3%) [19]. However, the prevalence of dyslipidemia in this study is higher than the previous findings reported in Eastern Ethiopia (34.8%) [11], Africa PLOS ONE (25.5%) [9], China (32.2%) [20], Iran (30.0%) [21], India (50.7%) [22], and Uganda (63.3%) [23]. Contrary to this, the prevalence is lower than previous studies reported in Lithuania (89.7%) [24], South Africa (85.0%) [25], India (78.4%) [26] and Poland (77.2%) [27].…”
Section: Plos Onesupporting
confidence: 91%
“…Africa (18.5%) [9]. Unlike many previous studies [22,30,38,[42][43][44][45], low HDL-C is the least prevalent component of dyslipidemia in this study. Advanced age, higher BMI, waking less than 150 minutes per week, raised FBG, and medium socio-economic status were significantly associated with a higher risk of dyslipidemia.…”
Section: Plos Onecontrasting
confidence: 65%
“…The prevalence of reduced HDL-C in this study, 50.7% is higher than the findings reported in Togo, 16.4% [ 5 ], Mekelle, 16.5% [ 18 ], China, 20.8% [ 1 ], and Durame, southern Ethiopia, 41.9% [ 15 ]. Whereas, it is lower than the findings from India, 62% [ 22 ], and Ethiopia, 68.7% [ 9 ]. These variations might be due to differences in cut-off values, distribution of risk factors, study setting, and socio-economic status of the participants.…”
Section: Discussioncontrasting
confidence: 58%
“…The overall prevalence of dyslipidemia reported in this study is consistent with the findings reported in Mekelle, 66.7% [ 18 ], and Durame, southern Ethiopia, 65.6% [ 15 ]. However, the prevalence is higher than the findings reported in Africa, 29.7% [ 4 ], Eastern Ethiopia, 34.8% [ 6 ], China, 43.3% [ 1 ], India, 50.7% [ 22 ], Iran, 51.8% [ 23 ], Sao Paulo, 59.74% [ 24 ], Nigeria, 60% [ 25 ], and Togo, 60.3% [ 5 ]. The reason for the high prevalence in this study might be attributed to differences in sample sizes, study setting, study population, socio-economic status, and lifestyle of the study participants [ 23 ].…”
Section: Discussionmentioning
confidence: 79%
“…It is quite common that atherosclerosis and blood vessel disease may develop even before diabetes is diagnosed. 11,12 The treatment of Rosuvastatin and Fenofibrates has altered the Serum Total Cholesterol, LDL, and TGL and subsequent gradual increase in HDL (Table 9). Lowering LDL has become a primary goal in cardiovascular prevention and commonly estimated from quantitative measurements of total and HDL-cholesterol and plasma triglycerides (TG) using the empirical relationship of Friedewald et al And also, LDL has been associated with the development of plaque deposits on artery walls, which narrow the passage and restrict blood flow.…”
Section: Resultsmentioning
confidence: 99%